ChemInform Abstract: Enantioselective Protonation of Alkenyl Trifluoroacetates Catalyzed by Chiral Tin Methoxide. Issue 18 (17th April 2014) - Yanagisawa, Akira; Sugita, Takuya; Yoshida, Kazuhiro
Abstract: Optically active ketones containing a tertiary stereogenic center at the α‐position are obtained by catalytic enantioselective protonation of alkenyl trifluoroacetates.